To the question of proverbs in the novels of Alexander Prokhanov (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article is devoted to the character of  proverbs using in the language of the modern writer Alexander Prokhanov's novels. The author of the article considers features of functioning in fiction both usual proverbs and sayings, and the occasional steady phrases, created by the writer with the definite purposes.
Keywords: proverbs; sayings; a stable phrase; praseological unit; usual; occasional